HUBUNGAN ASUPAN PROTEIN HEWANI, ZAT BESI DAN ASAM FOLAT DENGAN KADAR HEMOGLOBIN REMAJA PUTRI - Ida Bagus Setia Darma; Desak Putu Sukraniti; Gusti Ayu Dewi Kusumayanti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
One of the important nutritional problems in Indonesia is iron deficiency anemia which is often suffered mainly by young women. The result of Riskesdas (2013) showed that the prevalence of anemia in Indonesia is 21,7%. The purpose this research is to know the correlation between intake of animal protein, iron and folic acid with hemoglobin levels in young women in SMA Negeri 1 Ubud. This research type is observational with cross sectional design. The target population this research is 365. Samples numbered 76 people taken by multistage random sampling. Data of animal protein, iron, and folic acid collected by interview method using a form food recall 2x24 hour and check the levels of hemoglobin using Hb meter method. Data analysis use Correlation Pearson Product Moment with computerized system. The result of this research showed that the prevalence of anemia in young women in SMA Negeri 1 Ubud is 78,9% with an average hemoglobin levels of 10,8 gr/dl. Over animal protein intake than AKG as much 57 (75,0%) with an average of 34,3 gr. Less iron intake than AKG as much 76 (100,0%) with an average of 6,6 mg. Less folic acid intake than AKG as much 75 (98,7%) with an average of 120,9 mcg. There is significant correlation between the intake of animal protein and iron with hemoglobin levels of young women (p 0,05). There is no significant correlation between the intake of folic acid with hemoglobin levels of young women (p 0,05).Keywords: Animal Protein, Iron, Folic Acid, Hemoglobin